Students’ Motivational Factors behind Acquiring Shadow Education and Reasons for Creating New Generation Schools in Cambodia - Houn Thon; Sereyrath Em; Sina Pang; Ravy Nhor (Journal of General Education and Humanities, 2022)
The current study explores the motivational factors behind acquiring shadow education in Cambodia. We adopted documentary design, which is one of the qualitative methods. We collected relevant documents on shadowing in Cambodia and analyzed them qualitatively using the proposed content analysis. This study indicated that the leading motivational factors behind acquiring extra education in Cambodia were students' grades and overemphasis on examinations, school quality, teacher economic benefits, or teacher corruption. The findings from these studies could be used to discuss and generalize the motivational factors behind acquiring shadow education in the Cambodian educational context. Along with the existing shadow education, causing difficulty for the poor, the Royal Government of Cambodia and the Ministry of Education, Youth and Sports (MoEYS) have taken measures to eliminate this type of education by turning some schools into New Generation Schools (NGS).